2017
DOI: 10.1038/s41598-017-00877-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the association between UBAC2 polymorphisms and Behçet’s disease in a Japanese population

Abstract: Behçet’s disease (BD) is reportedly associated with polymorphisms of the ubiquitin-associated domain containing 2 (UBAC2) gene in Turkish, Italian, and Chinese populations. Here we investigated whether UBAC2 polymorphisms were associated with BD in a Japanese population. Using data from 611 Japanese BD patients and 737 Japanese controls who participated in our previous genome-wide association study, we analyzed the 58 genotyped single-nucleotide polymorphisms (SNPs) in the region 100 kb upstream and downstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The ubiquitin-associated domain-containing protein 2(UBAC2) gene is located on chromosome 13q32.3 and encodes UBAC2 protein that is a highly conserved protein in different species 6 , 7 . It was reported that the polymorphism of UBAC2 gene was related to Behcet’s disease and UBAC2 gene was the risk allele of Behcet’s disease 8 11 . The upregulation of UBAC2 expression can promote the progress of Behcet’s disease 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitin-associated domain-containing protein 2(UBAC2) gene is located on chromosome 13q32.3 and encodes UBAC2 protein that is a highly conserved protein in different species 6 , 7 . It was reported that the polymorphism of UBAC2 gene was related to Behcet’s disease and UBAC2 gene was the risk allele of Behcet’s disease 8 11 . The upregulation of UBAC2 expression can promote the progress of Behcet’s disease 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the polymorphism of UBAC2 gene was related to Behcet’s disease and UBAC2 gene was the risk allele of Behcet’s disease 8 11 . The upregulation of UBAC2 expression can promote the progress of Behcet’s disease 11 . Recently, a growing body of evidences demonstrated that UBAC2 was also closely related to the occurrence and development of malignant tumors, such as skin cancer and BC 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mammalian cells have shown that the UBAC2 in the ER also plays a role in cellular energy homeostasis through controlling cytoplasmic lipid droplet turnover (Suzuki et al, 2012;Wang and Lee, 2012;Olzmann et al, 2013). Polymorphisms in the UBAC2 gene have also been associated with Behcet's disease, a systemic inflammatory disorder in human (Sawalha et al, 2011;Hou et al, 2012;Yamazoe et al, 2017). Given the diverse and complex roles of UBAC2 proteins, it is likely that the evolutionarily conserved ER proteins participate in a range of cellular and molecular processes through distinct mechanisms and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies suggest that it may function in protein localization in the endoplasmic reticulum [127]. The association of the UBAC2 gene with BD was found in Turkish, Chinese, Italian, and Japanese populations [128][129][130][131]. Functionally, the presence of BD-risk rs9517723 allele was correlated with an increased expression of the UBAC2 gene.…”
Section: Ubac2mentioning
confidence: 99%